Impact of graft thickness reduction of left lateral segment on outcomes following pediatric living donor liver transplantation. Issue 9 (15th May 2018) - Kitajima, Toshihiro; Sakamoto, Seisuke; Sasaki, Kengo; Narumoto, Soichi; Kazemi, Kourosh; Hirata, Yoshihiro; Fukuda, Akinari; Imai, Rumi; Miyazaki, Osamu; Irie, Rie; Teramukai, Satoshi; Uemoto, Shinji; et al.
Abstract : Reducing graft thickness is essential to prevent large‐for‐size graft problems in pediatric living donor liver transplantation (LDLT). However, long‐term outcomes of LDLT using reduced‐thickness left lateral segment (LLS) grafts are unclear. In 89 patients who underwent LDLT using reduced LLS grafts between 2005 and 2017, short‐term and long‐term outcomes were compared between a nonanatomically reduced LLS (NAR‐LLS) graft group and a reduced‐thickness LLS graft group. Estimated blood loss was lower and abdominal skin closure was less needed in the recipient operation in the reduced‐thickness LLS graft group. Postoperatively, portal vein (PV) flow was significantly decreased in the NAR‐LLS graft group, and there was shorter intensive care unit (ICU) stay and fewer postoperative complications, especially bacteremia, in the reduced‐thickness LLS graft group. Graft survival at 1 and 3 years after LDLT using reduced‐thickness LLS grafts was 95.2% and 92.4%, respectively, which was significantly better than for NAR‐LLS grafts. Multivariate analysis revealed that fulminant liver failure, hepatofugal PV flow before LDLT, and NAR‐LLS graft were associated with poor graft survival. In conclusion, LDLT using reduced‐thickness LLS grafts is a safe and feasible option with better short‐ and long‐term outcomes in comparison with NAR‐LLS grafts. Abstract : In pediatric patients undergoing living donor liver transplantation with a reduced left lateral segment graft, reducing the graft thickness is strongly associated with better patient and graft survival in comparison to liver transplantation using a nonanatomically reduced graft.